Representation of Indonesian social and cultural ideology in the book Sahabatku Indonesia BIPA 2: A critical linguistic study - Muzaki, Helmi; Santoso, Anang; Martutik, Martutik; Isnaeni, Afiyahtun; Kusumawardani, Aulia Rachma; Bello, Idris Muhammad (Universitas Mulawarman, 2026)
This study aims to describe how Indonesian social and cultural ideologies are linguistically represented in the Sahabatku Indonesia BIPA 2 textbook through a Critical Linguistics perspective. The ideological dimension in textbooks, particularly how social, moral, and national values ​​are constructed through language choices, has rarely been studied in depth, necessitating an analysis capable of uncovering the role of language as a means of representing symbolic power in textbooks. This research method uses a descriptive qualitative approach with the Critical Linguistics analytical framework developed by Fowler. Data were obtained from reading texts, dialogues, and exercises in each learning unit and then analyzed at three levels: lexical choice, syntactic structure, and ideological discourse forms. The results show that this textbook consistently represents national values ​​such as mutual cooperation, social harmony, cleanliness, modernity, and cultural nationalism. These values ​​are conveyed through evaluative vocabulary choices, simple declarative and imperative sentences, and narratives that frame Indonesia as a developed, harmonious, and morally sound nation. This finding confirms that BIPA textbooks play a dual role: as a pedagogical tool and a cultural diplomacy tool that strengthens Indonesia’s image in the eyes of the international community.